2005
DOI: 10.1080/00365540500264050
|View full text |Cite
|
Sign up to set email alerts
|

Swedish guidelines for the management of community-acquired pneumonia in immunocompetent adults

Abstract: This document presents the evidence-based guidelines of the Swedish Society of Infectious Diseases for the management of adult immunocompetent patients with community-acquired pneumonia (CAP), who are assessed at hospital. The prognostic score 'CURB-65' is recommended for all CAP patients in the emergency room. The score provides an assessment tool for the decision regarding outpatient treatment or level of hospital supervision, the choice of microbiological investigations, and empirical antibiotic treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 164 publications
0
11
0
1
Order By: Relevance
“…To obtain complete data on mortality, the database was linked to Statistics Sweden using the unique personal identification number given to all Swedish citizens 19. The Swedish national guidelines on the clinical management of CAP published in 2005 recommend that all patients with suspected pneumonia assessed at a hospital should have a chest x-ray and two blood cultures performed 20. Treatment regimens should be based on the severity of pneumonia graded according to CURB-65 where patients with non-severe CAP (0–2 points) are recommended treatment with penicillin G, patients with 3 points are recommended treatment with penicillin G or a cephalosporin and patients with very severe CAP (4–5 points) are recommended treatment with a cephalosporin in combination with a macrolide or penicillin G in combination with moxifloxacin/levofloxacin.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain complete data on mortality, the database was linked to Statistics Sweden using the unique personal identification number given to all Swedish citizens 19. The Swedish national guidelines on the clinical management of CAP published in 2005 recommend that all patients with suspected pneumonia assessed at a hospital should have a chest x-ray and two blood cultures performed 20. Treatment regimens should be based on the severity of pneumonia graded according to CURB-65 where patients with non-severe CAP (0–2 points) are recommended treatment with penicillin G, patients with 3 points are recommended treatment with penicillin G or a cephalosporin and patients with very severe CAP (4–5 points) are recommended treatment with a cephalosporin in combination with a macrolide or penicillin G in combination with moxifloxacin/levofloxacin.…”
Section: Methodsmentioning
confidence: 99%
“…As sputum cultures may be contaminated by the oropharyngeal flora, so fibreoptic bronchoscopic techniques have been developed to enable collection of lower respiratory tract samples with minimal risk of contamination. At present, a major reason for fibreoptic bronchoscopy (FOB) in LRTI patients is failure to respond as expected to the first-line antibiotic treatment [2,3]. However, PRATS et al [4] demonstrated that the culture yield of Streptococcus pneumoniae and Haemophilus influenzae is rapidly reduced in lower respiratory tract secretions during antibiotic treatment; because of this, PRATS et al [4] and other groups [5,6] have suggested that FOB should be performed earlier in the course of LRTI, if possible prior to antibiotic treatment.…”
mentioning
confidence: 99%
“…According to the statistics, there were ~6.5–15 million persons suffering from CAP each year, among which over 200,000 persons died of CAP. All guidelines on CAP mentioned that imaging examination was the main examination means of CAP diagnosis and evaluation of therapeutic effects (1012). At present, there are a few reports on the studies on the application of VRI technology in CAP patients.…”
Section: Discussionmentioning
confidence: 99%